(untitled) (Research, Society and Development, 2021)
The frozen fruit pulp market has been growing in recent years, and for this market to continue expanding, it is essential that the product has satisfactory quality, especially from a microbiological point of view. As it is a food product with a high percentage of water in its composition, it has high perishability and a considerable amount of waste that can economically disadvantage the agro-industrial fruit pulp sector. Thus, the objective of this work was to evaluate the microbiological quality of frozen fruit pulps produced and marketed in the municipality of Limoeiro do Norte - EC. For this, 100 samples of frozen fruit pulps acquired in the commerce and in a producing company, of 11 different flavors, were submitted to microbiological analysis of totals coliforms and thermotolerant, mold and yeast count and Salmonella sp. All samples were in compliance with the legislation for total and thermotolerant coliforms, while 60% of the samples had mold and yeast counts above the permitted level (7.9 x 105 CFU/g). Detectou it is the presence of Salmonella sp. u ma pulp sample cashew flavor, obtained in a commercial establishment, being incompliance with the legislation in force, which determines that this microorganism should be absent. Therefore, it is concluded that due to inadequate microbiological quality , the producing company demonstrated hygienic-sanitary control, selection of raw materials and unsatisfactory storage conditions in the processing of frozen fruit pulps produced and marketed in Limoeiro do Norte - CE , and therefore, offering health risks to consumers.